If we have the system:
![\begin{gathered} 3x+y=-2 \\ ax+by=c \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wj11v6c6er5xkxss9t0h8pi1g1jtg0nmiq.png)
and we don't want the system to have a solution we need that one equation contradicts the other. For example if we choose a=3, b=1 and c=3, we have the system:
![\begin{gathered} 3x+y=-2 \\ 3x+y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pnuch0rk4s0li0qupskwb606pmpp3jbudi.png)
notice that the left side on both equations is the same, whereas the right side is not the same; this means that the second equation contradicts the first one, hence the system does not have a solution.
This form of choosing a, b and c can be extend to and infinite number of systems if we only change the value of c, that is, as long as a=3, b=1 and that c is not -2 the sytem will not have a solution.